THE EFFECT OF LEADERSHIP ON PERFORMANCE OF THE EMPLOYEES AT THE LABOR OFFICE OF NORTH SUMATRA PROVINCE - Batubara, Soulthan Saladin; Wulandari, Niken; Aulia, Liandra (Proceeding International Conference of Science Technology and Social Humanities, 2022)
This research aims to determine the Effect of Work Conflicts on Employee Performance at Labor Office of North Sumatera Province. The data analysis techniques used are regression analysis, t test, and coefficient of determination while tha data processed using SPSS (Statistical package for the Social Sciens) in version 16.0 for windows. The results of the study obtained showed that leadership has a positive and significant influence on the performance of the proven t value with a probability of sig 0.000, smaller than α = 0.05. Furthermore, the coefficient of determination measured using R square is 0.240 (24.0%).